Online Learning at Early Pandemic Situation: Grassroots Voices - Prasetianto, Mushoffan; Maharddhika, Rizkiana; Ruminar, Hafida; Prasetyaningrum, Dian Islami (Jurnal Pendidikan Indonesia, 2021)
The advent of the COVID-19 pandemic reconfigured several aspects of life, one of which is education. A study on grassroots voices on online learning is a dearth of. Therefore, a present study was addressed to uncover teachers’ and students’ voices in online learning. Questionnaires and interviews were employed to garner data. 233 students and 30 teachers’ responses from questionnaires were obtained. The interviews were conducted to obtain in-depth data. The data were interpreted descriptively. The results showcased that students’ voices on the ease of GC and GC performance were positive, yet institution support was not maximally implemented. Simultaneously, the teachers’ voices on the ease of GC, the performance of GC, and the supports of institution were positive. In a nutshell, teachers and students have a positive impression of online learning. Their positive impression comes from the ease of the online platform operation, the online platform’s good performance, but student views that the institutional support is not maximally implemented. The ease of using online platforms should be considered in choosing one of the various online platforms available. The online platform features are not complicated for students and teachers to easily operationalize the online platform and support teaching and learning activities such as delivering materials, assigning tasks, submitting a task, and assessing tasks.